Posterior reversible encephalopathy syndrome (PRES) presenting as Status Epilepticus in a case of Autoimmune Hemolytic Anemia (AIHA): A Case report - Sameera Dronamraju (Asian Journal of Medical Sciences, 2021)
Posterior reversible encephalopathy syndrome (PRES) is a neurotoxic state, caused by imbalance in autoregulation of posterior cerebral circulation. We report a case of young female, presented at emergency department with complains of nausea, vomiting and generalized tonic clonic seizures prior to admission. During the course of hospital stay patient landed in status epilepticus which was treated appropriately. Patient’s magnetic resonance imaging (MRI) was done which had classical features of vasogenic edema in occipital and parietal region, suggestive of PRES. She was a known case of autoimmune hemolytic anemia that was treated with multiple blood transfusions and low dose oral steroids. She was discharged after complete resolution of symptoms with the advice to follow up in medicine outpatient department. Our case describes about autoimmune hemolytic anemia in which occurrence of PRES is uncommon. Early diagnosis and robust treatment can prevent permanent damage to the brain, and is often associated with complete recovery.